2002
DOI: 10.1103/physreve.66.051604
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of low anisotropy morphologies in directional solidification

Abstract: We report experimental results on quasi-two-dimensional diffusion limited growth in directionally solidified succinonitrile with small amounts of poly(ethylene oxide), acetone, or camphor as a solute. Seaweed growth, or dense branching morphology, is selected by growing grains close to the [111] plane, where the in-plane surface tension is nearly isotropic. The observed growth morphologies are very sensitive to small anisotropies in surface tension caused by misorientations from the [111] plane. Different seaw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 38 publications
(59 reference statements)
6
35
1
Order By: Relevance
“…Rotations of 360°m ake it possible to determine additional symmetries (e.g., twofold) which are often overlooked, yet can have important effects. [11][12][13] Using this technique, it is possible to select a particular orientation or study the growth over a range of orientations as shown here. Note that the large aspect ratio cells are valuable in these studies since there must be a sufficient area for the sample to grow and rotate without encountering the boundaries of the cell.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Rotations of 360°m ake it possible to determine additional symmetries (e.g., twofold) which are often overlooked, yet can have important effects. [11][12][13] Using this technique, it is possible to select a particular orientation or study the growth over a range of orientations as shown here. Note that the large aspect ratio cells are valuable in these studies since there must be a sufficient area for the sample to grow and rotate without encountering the boundaries of the cell.…”
Section: Resultsmentioning
confidence: 97%
“…In this case, a rotation beyond 90°is not necessary. It is known, however, that there can be nonfourfold symmetries [11][12][13] in 2D interfacial growth. Incorporating the ability to rotate a full 360°allows for the determination of sample orientation and all in-plane crystal symmetries.…”
Section: Introductionmentioning
confidence: 98%
“…For a certain crystallographic direction, for example, the <100> direction for a cubic crystal, the surface energy is anisotropic [17], and the morphology develops with cellular or dendritic patterns. Meanwhile, for crystalline axes along <111> direction, the surface energy is isotropic [18]; the interface development has been dominated by seaweed growth [2]. There have been several suggestions as to how to incorporate anisotropy into the phase field description.…”
Section: Phase Field Modeling On Morphology Developmentmentioning
confidence: 99%
“…It appears that the main branch and the secondary arm are locally symmetric about the axis of temperature gradient. Such interface morphology with a slight degeneracy is called degenerate seaweed according to Utter and Bodenschatz [18].…”
Section: Phase Field Modeling On Morphology Developmentmentioning
confidence: 99%
See 1 more Smart Citation